Enhancing a Mechatronics design distance-learning course through internet and Web 2.0 technologies. (2nd August 2010) - Gan, W.C.; Tse, Sandy; Kwok, Paul C.K.; Tsang, Jonathan C.M.; , Gary Lam
Mechatronics is a newly developed multi-disciplinary engineering subject. Students sometimes find that it is quite difficult to master this area of focus because of its demand for wide range of knowledge in engineering required. In addition, the distance-learning mode presents the geographical and time barrier for students. In the last decade, new Web 2.0 technology was developed rapidly; the proper use of these new technologies can help arouse students' interest in learning a Mechatronics course. In this paper, the use of internet and Web 2.0 technologies to enhance the teaching and learning effectiveness in a Mechatronics distance-learning course will be discussed.